Modal analysis of dissimilar metal (steel and aluminium) joint by spot wleding - Mohd Fadhli, Che Ismail (2013)
This project report deals with dynamic behaviour of joining between stainless steel and aluminium alloy by Spot welding using theoretical and experimental analysis method. The structural three-dimensional solid modelling of joining between stainless steel and aluminium alloy by welding was developed using the drawing software. The finite element model of the components was analysed using the linear modal analysis approach. Finally, the experimental modal analysis was performed using Impact Hammer Testing method. The natural frequency of the mode shape is determined and comparative study was done from both method results. The comparison between natural frequencies of finite element modelling and model testing shows the closeness of the results. From the results, the percentage error had been determined and the limitation in the natural frequency of the joining between stainless steel and aluminium alloy by welding is observed. The results of this project shown the mode shape of the joining plate by Spot welding for simulation are generally is not in agreement with the experimental value and the frequencies of the experimental modal analysis are a bit different with the frequencies of the simulation. The percentage error is bit high because there are some errors occur during the experimental modal analysis. The experimental modal analysis is conducted with fix condition of the joining plate between aluminium alloy and stainless steel by welding and the effect of damping which effect test rig by using polystyrene as a base of the plate is a factors as the higher percentage error. It is conclude that the in experimental method uses the polystyrene as a base affected the result. Experimental operating deflection shape also conducted and compare with calculation method to get a dominant mode shape when 53.3 Hz will give. Mode one show a dominant mode in ods. The result shows joining between aluminium and steel by Spot drawn to welding–brazing because of their difference in melting point and the natural frequency comparison shows the closeness of the result between experimental modal analysis and FEA.